2002
DOI: 10.1038/nn915
|View full text |Cite
|
Sign up to set email alerts
|

Greater plasticity in lower-level than higher-level visual motion processing in a passive perceptual learning task

Abstract: Simple exposure is sufficient to sensitize the human visual system to a particular direction of motion, but the underlying mechanisms of this process are unclear. Here, in a passive perceptual learning task, we found that exposure to task-irrelevant motion improved sensitivity to the local motion directions within the stimulus, which are processed at low levels of the visual system. In contrast, task-irrelevant motion had no effect on sensitivity to the global motion direction, which is processed at higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
198
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 193 publications
(210 citation statements)
references
References 44 publications
11
198
1
Order By: Relevance
“…However, training in clear displays requires the system to work to reduce internal limitations (or equivalently amplify the stimulus) but also provides good information about the nature of the target stimulus or the perceptual template. Although an optimized template is far more critical in noisy displays, template tuning may nonetheless occur in low-noise training by optimization of information about the stimulus, ¶ or possibly by repetitive task-relevant exposure to the signal stimuli (25,26). Training the template in (lowcontrast) low-noise displays may be sufficient to optimize the filtering of external noise substantially, especially when the external noise is white.…”
Section: Discussionmentioning
confidence: 99%
“…However, training in clear displays requires the system to work to reduce internal limitations (or equivalently amplify the stimulus) but also provides good information about the nature of the target stimulus or the perceptual template. Although an optimized template is far more critical in noisy displays, template tuning may nonetheless occur in low-noise training by optimization of information about the stimulus, ¶ or possibly by repetitive task-relevant exposure to the signal stimuli (25,26). Training the template in (lowcontrast) low-noise displays may be sufficient to optimize the filtering of external noise substantially, especially when the external noise is white.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ahissar and Hochstein (2002) found that subjects' learning to detect a target within a horizontally or vertically elongated array does not transfer to a feature of the array they do not attend, namely, the orientation of the array. Although Watanabe and his colleagues (Watanabe et al, 2001(Watanabe et al, , 2002Seitz and Watanabe, 2003) have shown that it is not necessary for attention to be directed to a visual feature for that feature to be learned, they admit that attention plays an important role in perceptual learning (Seitz and Watanabe, 2005).…”
Section: Changes In Attention-related Areas During Perceptual Learningmentioning
confidence: 99%
“…Fourth, is task involvement during training necessary for the observed shift in neural sites? It has been shown that perceptual learning of a feature results from not only training on a task on the feature but also exposure to the feature that is irrelevant to the task (17)(18)(19). It would be highly interesting to test whether the transfer observed in this study and associated neural shifts occur as a result of mere exposure to 100% coherent motion task-irrelevant.…”
mentioning
confidence: 86%